Implementation Method Forward Chaining in Game Puzzle (Case Study in Paud Dini Laras Yogyakarta) - Azhari, Ahmad; Dharma Ariawan, Ade (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
In the early childhood education stage, children will tend to be more interested in easy-to-play games that have animated images that attract attention. Whereas currently in learning PAUD children still use the game method using paper media so that the games provided will make children feel bored. This study aims to conduct a new teaching media approach namely Puzzle educational games using the Forward Chaining method as a research topic on compiling desktop-based images and games for PAUD children at DUD Laras Yogyakarta. This research uses Forward Chaining method as an implementation in a Puzzle Game that is R1 is the first rule that is known fact is the Random Puzzle box contained in each scene, R2 is the 2nd rule of the reasoning process when the matching premise is wrong then there is a temporary premise namely the trash box that hold until all the premises are properly matched, R3 is the 3rd rule that is the time and score as a conclusion the game can continue until the game is finished. This research resulted in 2 times Game testing. The first test using black box testing game application is correct and has no malfunction on the button and is feasible to be implemented. And the second test is the quality testing that has been done by testing the choice of answer categories from the questionnaire that has been distributed in the field, it can be concluded that the Puzzle Game is made easy to use and has a pretty good appearance and content suitable for early childhood play (PAUD).